Energy Efficiency Analysis of Main Cooling Pump System on Bulk Carrier Using VSD - Fajri Ashfi Rayhan; Rashieka Alma (Naval Architecture Department, Kalimantan Institut of Technology, 2026)
Improving energy efficiency in marine auxiliary systems has become increasingly important due to rising fuel consumption, stricter environmental regulations, and global green shipping initiatives. Conventional seawater cooling pumps on bulk carrier vessels generally operate at constant speed regardless of cooling demand, resulting in excessive energy consumption under partial-load conditions. Previous studies mainly focused on general Variable Speed Drive (VSD) applications, while limited research investigated the integrated performance of seawater cooling systems in bulk carriers, particularly the relationship between pump energy consumption, heat transfer performance, and operational efficiency. This study was conducted to evaluate the energy efficiency of the main cooling pump system on a bulk carrier vessel through the implementation of a Variable Speed Drive (VSD). The analysis was conducted using a thermodynamic simulation approach under steady-state conditions by applying pump affinity laws, heat transfer equations, and operational data from a MAN B&W S42MC marine diesel engine under various engine loads and seawater temperatures. The results show that VSD implementation reduced pump power consumption from approximately 26 kW to 2–10 kW under partial-load conditions, corresponding to improved pump efficiency, with a maximum efficiency of approximately 82% achieved near the Best Efficiency Point (BEP). The cooling system also maintained stable freshwater outlet temperatures around 36°C, indicating effective heat transfer performance, thermal stability, and improved cooling system energy efficiency. These findings confirm that VSD operation is highly effective under partial-load conditions and supports ship energy management systems to reduce fuel consumption and support sustainable green shipping practices.